The PDE4DIP-AKAP9 axis promotes lung cancer growth through modulation of PKA signalling - Yangyang Fu; Shishun Huang; Rulu Pan; Xingan Chen; Ting Liu; Rongzhe Zhang; Fangsheng Zhu; Qiwei Fang; Liyue Wu; Juji Dai; Ouchen Wang; Liting Lu; et al. (Communications Biology)
Abstract Phosphodiesterase 4D interacting protein (PDE4DIP) is a Golgi/centrosome-associated protein that plays critical roles in the regulation of microtubule dynamics and maintenance of the Golgi structure. However, its biological role in human cancer remains largely unknown. In this study, we showed that PDE4DIP is overexpressed in human non-small cell lung cancer (NSCLC) tissues and that upregulated PDE4DIP expression is associated with poor prognosis in patients with lung cancer. We demonstrated that PDE4DIP knockdown inhibits NSCLC cell proliferation in vitro and tumorigenicity in vivo. We further demonstrated that PDE4DIP knockdown triggers apoptosis and cell cycle arrest in NSCLC cells by activating the Protein kinase A (PKA) /CREB signalling pathway. PDE4DIP coordinates with A-kinase anchoring proteins 9 (AKAP9) to enhance the Golgi localization and stability of PKA RIIα. Depletion of PDE4DIP mislocalizes PKA RIIα from the Golgi and leads to its degradation, thereby compromising its negative regulatory effect on PKA signalling. Overall, our findings provide novel insights into the roles of the PDE4DIP-AKAP9 complex in regulating PKA signalling and NSCLC growth and highlight PDE4DIP as a promising therapeutic target for NSCLC.